Prevalence, sex differences, and implications of pulmonary hypertension in patients with apical hypertrophic cardiomyopathy - Anand, Vidhu; Covington, Megan K.; Saraswati, Ushasi; Scott, Christopher G.; Lee, Alexander T.; Frantz, Robert P.; Anavekar, Nandan S.; Geske, Jeffrey B.; Arruda-Olson, Adelaide M.; Klarich, Kyle W. (Frontiers in Cardiovascular Medicine, 2024)
Introduction: Apical hypertrophic cardiomyopathy (ApHCM) is an HCM subtype present in upto 25% of Asian patients and is less well understood in non-Asian patients. While ApHCM has been considered a more "benign" variant, it is associated with increased risk of atrial and ventricular arrhythmias, apical thrombi, stroke, and progressive heart failure. Pulmonary hypertension (PH) has been reported in ApHCM due to elevated left sided pressures, but its prevalence and sex differences are unknown.We sought to evaluate the prevalence, risk associations, and sex differences in elevated pulmonary pressures in the largest cohort of patients with ApHCM at a single tertiary center. A total of 542 patients with ApHCM were identified using ICD codes and clinical notes searches, confirmed by cross referencing with cardiac MRI reports extracted by Natural Language Processing and manual chart and imaging review.: Pulmonary artery systolic pressure (PASP) by echocardiogram at the time of diagnosis was available in 414 patients. Mean age was 59.4±16.6 years, with 181 (44%) being females. Mean PASP was 38±12 mmHg in females vs 33±9 mmHg in males (p <0.0001). PH as defined by PASP > 36 mm Hg was present in 140/414 (34%) patients, with a predominance in females (79/181 (44%)) vs males (61/233 (26%), p <0.0001). Female sex, atrial fibrillation, diagnosis of congestive heart failure and elevated filling pressures on echocardiogram remained significantly associated with PH (PASP > 36 mm Hg) in multivariable modeling. PH, when present, was independently associated with mortality (Hazard ratio 1.63, 95% CI (1.05-2.53), p=0.028) and symptoms (odds ratio 2.28 (1.40, 3.71), p<0.001). Conclusion: PH was present in 34% of patients with ApHCM at diagnosis, with female sex predominance. PH in ApHCM was associated with symptoms and increased mortality.